2010
DOI: 10.1016/j.ajog.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia induces inducible nitric oxide synthase gene expression and consequent nitrosative stress via c-Jun N-terminal kinase activation

Abstract: Objective-Maternal diabetes adversely impacts embryonic development. We test the hypothesis that hyperglycemia-induced JNK1/2 activation mediates iNOS induction.Study Design-Levels of iNOS mRNA and nitrosylated protein were determined in cultured C57BL/6J conceptuses exposed to hyperglycemia (300 mg/dl glucose) and C57BL/6J embryos exposed to streptozotocin-induced diabetes. iNOS-luciferase activity and endogenous reactive nitrogen species were determined in transfected PYS-2 (mouse teratocarcinoma) cells expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 23 publications
5
55
1
1
Order By: Relevance
“…Maternal diabetes-induced ROS react with iNOS-induced nitric oxide to generate RNS, which cause to a severe form of oxidative stress, nitrosative stress 23 . To explore whether curcumin treatment blocks high glucose-induced oxidative and nitrosative stress, we assessed the levels of 4-HNE, a lipidperoxidation marker and nitrotyrosine-modified protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal diabetes-induced ROS react with iNOS-induced nitric oxide to generate RNS, which cause to a severe form of oxidative stress, nitrosative stress 23 . To explore whether curcumin treatment blocks high glucose-induced oxidative and nitrosative stress, we assessed the levels of 4-HNE, a lipidperoxidation marker and nitrotyrosine-modified protein.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress-induced kinase signaling triggers ER stress in the developing embryo, leading to NTD formation 19 . iNOS expression and its associated nitrosative stress are induced by maternal diabetes, and deletion of the iNos gene alleviates NTD formation in diabetic pregnancies 23 . Maternal diabetes-induced specific PKC isoform activation is a key component of the causal events in NTD formation 18, 24 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Indeed, it has been shown that hyperglycemia stimulates iNOS gene expression and nitrosative stress in diabetic embryopathy and activation of c-Jun N-terminal kinases 1 and 2 (JNK1/2) appears to play a key role in this process. 26 However, further studies are warranted to establish causality between hyperglycemia and leukocyte NOS2 overexpression in GDM women in the context of nitrosative stress. It is of note that several studies have reported iNOS overexpression in metabolic tissues of both dietary and genetic models of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NOS uncoupling and tetrahydrobiopterin deficiency contribute to the inflammatory and abnormal cytokine milieu in the vasculature (71). Furthermore, hyperglycemia significantly elicits the expression of cytokine-inducible NOS (iNOS) both in vitro and in vivo (36,118). Indeed, hyperglycemia induced by streptozotocin in Nos2 gene knockout mice led to diabetic cardiomyopathy, and sepiapterin, an inhibitor of NOS uncoupling, improved systolic FIG.…”
Section: Inflammation and Oxidative Stress In Endothelial Dysfunctionmentioning
confidence: 99%